2019
DOI: 10.1002/brb3.1285
|View full text |Cite
|
Sign up to set email alerts
|

A clinical case–control comparison of epidermal innervation density in Rett syndrome

Abstract: Introduction Rett syndrome (RTT), a rare neurodevelopmental disorder occurring primarily in females (1:10–15,000 female live births), is most often caused by loss‐of‐function mutations in the X‐linked methyl‐CpG‐binding protein 2 gene ( MECP2 ). Clinical observations and preclinical findings indicate apparent abnormal sensory and nociceptive function. There have been no direct investigations of epidermal sensory innervation in patients with RTT. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…Although quantitative sensory testing does not localize pathology along the somatosensory axis, our preliminary observations specific to small unmyelinated fibers indicate possible peripheral involvement based on epidermal nerve density values consistent with the preclinical model. 22,23 The lack of response to heat stimulus, along with repeated mechanical stimulation being the highest score, were similar to those in preclinical experimental models at the sensory modality (mechanical, heat) construct level, though we did not see the same patterns for cool and pressure. 22,24 There are important procedural differences in specificity and precision, though.…”
Section: Discussionsupporting
confidence: 62%
“…Although quantitative sensory testing does not localize pathology along the somatosensory axis, our preliminary observations specific to small unmyelinated fibers indicate possible peripheral involvement based on epidermal nerve density values consistent with the preclinical model. 22,23 The lack of response to heat stimulus, along with repeated mechanical stimulation being the highest score, were similar to those in preclinical experimental models at the sensory modality (mechanical, heat) construct level, though we did not see the same patterns for cool and pressure. 22,24 There are important procedural differences in specificity and precision, though.…”
Section: Discussionsupporting
confidence: 62%
“…Two recent studies showed marked skin hyperinnervation [59], and mechanical hypersensitivity in one male rat model proposed to study RTT, and somatosensory and viscerosensory alteration in female rats of the same model [59,60]. In striking agreement, another study demonstrated increased sensory fiber innervation in skin biopsies from RTT patients [61]. In RTT people, somatosensory disturbances may range from elevated pain threshold or heat insensitivity [62] to hypersensitivity [63,64].…”
Section: Discussionmentioning
confidence: 77%
“…In line with these rodent studies, a recent paper investigated potential abnormalities in peripheral somatosensory neuron innervation of the skin in patients with Rett syndrome. Skin biopsies from subjects with Rett syndrome exhibited an increased number of total epidermal sensory neuron fiber density as well as increased density of peptidergic, calcitonin gene-related peptide-positive fibers (Symons et al, 2019). Lastly, hyperexcitability of trigeminal neurons that innervate the jaw and facial muscles has also been observed in Mecp2 knockout mice, which was linked to alterations in sodium and potassium channel function (Oginsky et al, 2017).…”
Section: V2: Mecp2mentioning
confidence: 99%